Assessment of the accuracy of patient-specific drilling guides for cervical (C5–C6) and lumbar (L4–L5) vertebrae in cats - Costa, Rodrigo Casarin [UNESP] (2025)
Ten sets of vertebral biomodels and the corresponding drilling guides were created to evaluate the implantation accuracy in the cervical (C5–C6) and lumbar (L4–L5) vertebrae of cats. Smooth pins were implanted using the guides on the right side of five randomly assigned biomodel sets and on the left side of the remaining sets, with the contralateral side undergoing freehand implantation. Subsequently, a new tomographic study was conducted to measure the implantation angles. The pre-implantation angles were compared with the post-implantation angles between the techniques and among the sets. The guide-assisted implantation exhibited a lower dispersion compared to the freehand technique, with coefficients of variation of –1.95 and 48.9 in the cervical vertebrae and 1.98 and 9.39 in the lumbar vertebrae, respectively. However, no statistical difference was observed between the pre- and post-implantation angles, nor when comparing the vertebral segments (P > 0.05). Under the study conditions, the use of the guide failed to result in more accurate implantations in the C5–C6 and L4–L5 vertebral biomodels of cats.